Institutional networks and self-organized adaptation: Tracing the democratic architectures of climate response - Fischer, Harry; Khatri, Dil; Fleischman, Forrest; Gupta, Divya; Shrestha, Suchita; Devkota, Kamal; Bulkunde, Roshani; Singh, Devanshi; Adhikari, Binod; Pandey, Parbati; Rana, Rajesh; Guleria, Vijay (Swedish University of Agricultural Sciences, 2025)
This project, “Institutional Networks and Self-organized Adaptation”, examines the role of rural institutions and public support systems in shaping responses to shocks and stressors in rural India & Nepal during 2020-21. We include stressors related to COVID-19, climate, health, and other challenges identified by rural households.

The data includes:

- Village information on demographics, infrastructure, and natural resources
- Village level institutions involved in livelihood support and adaptive responses
- Networks of interaction between these institutions
- Household information on demographics, livelihoods, interaction with institutions, shocks & stressors, and responses to these stressors

Household level data includes high-frequency repeat visits (approximately monthly) to gather detailed information about stressors and responses over the calendar year.

This dataset contains 480 households nested within 16 local governmental units in the Himalayan region. This includes 8 villages in the Kangra District of India’s northern state of Himachal Pradesh and the Dhulikhel and Ramechhap Districts of east central Nepal.

Through repeated visits during the calendar year, we have captured 8694 self-observed shocks and stressors, i.e. "threats" (3550 in India & 5144 in Nepal), and 5859 responses to cope or adapt to these threats (2553 in India, 3306 in Nepal).
Institutionella nätverk och självorganiserande anpassning: Att spåra den demokratiska arkitekturen för klimatrespons
Keywords: RURAL DEVELOPMENT; LANDSBYGDSUTVECKLING; CLIMATE CHANGE; KLIMATFÖRÄNDRINGAR; COVID-19; COVID-19; climate adaptation; climate adaptation; social vulnerability; social vulnerability; shocks and stressors; shocks and stressors; governance; governance; sustainable development; sustainable development; Economic conditions and indicators; Ekonomiska förhållanden och indikatorer; Natural landscapes; Naturlandskap; Government, political systems and organisations; Regering, politiska system och organisationer; Social conditions and indicators; Sociala förhållanden och indikatorer; Social Sciences; Samhällsvetenskap; Human Geography; Kulturgeografi; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap